An offline predictive feedrate scheduling method for parametric interpolation considering the constraints in trajectory and drive systems. Issue 9 (April 2016) - Lu, Lei; Zhang, Lei; Ji, Shijun; Han, Yanjun; Zhao, Ji
Abstract The ability of drive unit limits the velocity, acceleration, and jerk of the axis, and the process and tool path geometry constrain the feedrate, acceleration, and jerk of the trajectory. It is of great difficulty and importance to schedule a suitable feedrate profile to achieve the higher machining efficiency and satisfy all the constraints. Due to the complexity of the feedrate scheduling algorithm, this paper presents an offline predictive feedrate scheduling method considering the constraints of trajectory system and drive system. The constraints in the drive system are transformed to the trajectory system appropriately, which reduces the difficulty of feedrate scheduling. The one-dimensional high-order time-optimal problem is solved by a numerical calculation method according to the bang-bang control method. The predictive method is applied to find the switching points of the jerk. Then a time-optimal feedrate profile under all the constraints is obtained. Both simulations and experiments are carried out to prove the effectiveness of the proposed offline predictive feedrate scheduling method.